Cannabidiol‐mediated RISK PI3K/AKT and MAPK/ERK pathways decreasing reperfusion myocardial damage - Antonio Franco‐Vadillo; Mireille Toledo‐Blass; Zeltzin Rivera‐Herrera; Gustavo Guevara‐Balcazar; Oscar Orihuela‐Rodriguez; Jose A. Morales‐Carmona; Alexandre Kormanovski‐Kovzova; Pedro Lopez‐Sanchez; Ivan Rubio‐Gayosso; Maria del Carmen Castillo‐Hernandez (Wiley, 2021)
Abstract Myocardial ischemia continues to be the first cause of morbimortality in the world; the definitive treatment is reperfusion; however, this action causes additional damage to ischemic myocardial tissue; this forces to seek therapies of cardioprotection to reduce this additional damage. There are many cardioprotective agents; within these, cannabinoids have shown to have beneficial effects, mainly cannabidiol (CBD). CBD is a non psychoactive cannabinoid. To evaluate the effect in experimental models of CBD in myocardial ischemia reperfusion in rats, twelve‐week‐old male rats have been used. The animals were divides in 3 groups: control(C), ischemia reperfusion (IR) and CBD pretreatment (1/day/5mg/kg /10days). Langendorff organ isolate studies were performed, and the area of infarction was assessed with triphenyl tetrazolium, in addition to molecular analysis of AT1 and AT2 receptors and Akt and Erk proteins and their phosphorylated forms related to RISK pathways. It was observed that there is an improvement with the use of CBD increasing inotropism and cardiac lusitropism, improving considerably the cardiovascular functionality. These could be related to the reduction of the area of infarction and activation of the AT2 receptor and the RISK pathway with absence of activation of the AT2 receptor (these could relate the reduction of the infarct area and the restoration of cardiovascular function with the activation of the AT2 receptor and the RISK pathway with the absence of activation of the AT2 receptor). The use of cannabinoids was shown to have beneficial effects when used as a treatment for myocardial reperfusion damage.